Treatment of child abuse : common ground for mental health, medical, and legal practitioners - Reece, Robert M.; Hanson, Rochelle F., 1962-; Sargent, John, 1947- (The Johns Hopkins University Press, 2014)
Acclaimed as a milestone resource by the Journal of Child and Family Studies, Treatment of Child Abuse has been updated and expanded with ten completely new chapters. The second edition adds the expertise of co-editors Rochelle F. Hanson, Ph. D., and John Sargent, M.D., along with chapters from many new contributors.